2016
DOI: 10.1007/s11682-016-9580-z
|View full text |Cite
|
Sign up to set email alerts
|

Are there gender differences in young vs. aging brains under risk decision-making? An optical brain imaging study

Abstract: Few research publications have reported on gender-dependent neural correlates of risk decision-making in older adults. In this study, we utilized functional near-infrared spectroscopy (fNIRS) to comprehensively investigate both age- and gender-dependent differences in neural correlates in response to a well-utilized risk decision-making protocol, the Balloon Analog Risk Task (BART). A newly-developed technique, atlas-guided diffuse optical tomography (atlas-DOT), was used to image the prefrontal cortices (PFC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
4
17
0
1
Order By: Relevance
“…Similar behavioral performance with significant sex-related differences in the underlying brain activation patterns while performing cognitive tasks both in healthy (e.g., Bell et al, 2006;Li et al, 2017;Riley et al, 2018) and patients suffering from different pathological conditions (e.g., Kasher et al, 2019) had been previously reported. These contradictory findings seem to be supported by a sex-related distinct functional brain organization favoring adaptive processing strategies that converge into the goal of maximizing efficient use of task-demanded cognitive resources.…”
Section: Contribution Of the Present Papersupporting
confidence: 77%
“…Similar behavioral performance with significant sex-related differences in the underlying brain activation patterns while performing cognitive tasks both in healthy (e.g., Bell et al, 2006;Li et al, 2017;Riley et al, 2018) and patients suffering from different pathological conditions (e.g., Kasher et al, 2019) had been previously reported. These contradictory findings seem to be supported by a sex-related distinct functional brain organization favoring adaptive processing strategies that converge into the goal of maximizing efficient use of task-demanded cognitive resources.…”
Section: Contribution Of the Present Papersupporting
confidence: 77%
“…44 The measured activation patterns can only be projected onto structural MRI, which is performed on the individual subject, when external landmarks are required for cranio-cerebral correlations with the 10 − 10∕10 − 20 electrode placement system. 45 An approach would be to create a finite element for a standard brain template [46][47][48] or subject-specific MR scans, 49,50 which forward model considering different optical properties for each brain layer, which could minimize the reconstruction errors and improve spatial accuracy.…”
Section: Image Qualitymentioning
confidence: 99%
“…57 The present work allows a GLM analysis voxel-by-voxel over reconstructed DOT images for each molecule HbO and HbR to be made, unlike other authors who applied GLM analysis prior to the reconstruction of the images. 46,48 …”
Section: Use Of Canonical Statistical Parametric Mappingmentioning
confidence: 99%
“…Por otra parte, al analizar el desempeño de los adultos emergentes en la toma de riesgo bajo distintos estados emocionales, en primer lugar, observamos que los hombres, independientemente del tipo de inducción emocional, tomaron más riesgos que las mujeres. Este sesgo en función del sexo para el comportamiento de riesgo también ha sido reportado por otros grupos (Li et al, 2016;Pilatti, Rivarola Montejano et al, 2017). Al respecto, distintos estudios han evidenciado diferencias neuroanatómicas, neurocognitivas y neuroendócrinas específicas en función del sexo durante el desarrollo, desde la niñez a la adultez emergente (Gur y Gur, 2016;Herting et al, 2018;Ingalhalikar et al, 2014;Peper, Koolschijn y Crone, 2013;Roalf et al, 2014).…”
Section: Discussionunclassified